Frailty syndrome in rheumatoid arthritis and symptomatic osteoarthritis: an emerging concept in rheumatology - Salaffi, Fausto; Farah, Sonia; Di Carlo, Marco (Acta Biomedica Atenei Parmensis, 2020)
Musculoskeletal conditions such as rheumatoid arthritis (RA) and symptomatic osteoarthritis (OA) were the leading cause of disability in developed countries and disproportionately affects older adults. Frailty is an emerging concept in rheumatology, which represents an important construct to aid in the identification of in- dividuals who are vulnerable to adverse events and less favourable outcomes. The prevalence of frailty among the community-dwelling population increases with age: it ranges from 7% to 10% in those aged over 65 years and to 20–40% among octogenarians. Among patients with RA, the prevalence of frailty is comparable to, or even greater, that of older geriatric cohorts and pre-frailty, a condition including a major health vulnerability between robust and frail, is much more prevalent in RA than in geriatric cohorts. Clinical OA is also associated with frailty and pre-frailty in older adults in European countries. The overall prevalence of clinical OA at any site was 30.4%; frailty was present in 10.2% and pre-frailty in 51.0 %. The diagnosis of frailty is usually clinical and based on specific criteria, which are sometimes inconsistent. Therefore, there is an increasing need to identify and vali- date robust biomarkers for this condition. In the literature, different criteria have been validated to identify frail older subjects, which mainly refer to two conceptual models: the Physical Frailty (PF) phenotype proposed by Fried and the cumulative deficit approach proposed by Rockwood. The purpose of this review was to quantita- tively synthesize published literature on the prevalence of frailty in RA and OA and summarize current evidence on the validity and practicality of the most commonly used screening tools for frailty.